Role of extracellular calcitonin gene-related peptide in spinal cord mechanisms of cancer-induced bone pain. Issue 3 (March 2016) - Hansen, Rikke R.; Vacca, Valentina; Pitcher, Thomas; Clark, Anna K.; Malcangio, Marzia
Abstract : Abstract: Severe pain is a common and debilitating complication of metastatic bone cancer. Current analgesics provide insufficient pain relief and often lead to significant adverse effects. In models of cancer-induced bone pain, pathological sprouting of sensory fibers at the tumor-bone interface occurs concomitantly with reactive astrocytosis in the dorsal horn of the spinal cord. We observed that calcitonin gene-related peptide (CGRP)-fiber sprouting in the bone was associated with an increase in CGRP content in sensory neuron cell bodies in the dorsal root ganglia (DRG) and increased basal and activity-evoked release of CGRP from their central terminals in the dorsal horn. Intrathecal administration of a peptide antagonist (α-CGRP8-37) attenuated referred allodynia in the hind paw ipsilateral to bone cancer. CGRP receptor components (CLR and RAMP1) were up-regulated in dorsal horn neurons and expressed by reactive astrocytes. In primary cultures of astrocytes, CGRP incubation led to a concentration-dependent increase of forskolin-induced cAMP production, which was attenuated by pretreatment with CGRP8-37. Furthermore, CGRP induced ATP release in astrocytes, which was inhibited by CGRP8-37. We suggest that the peripheral increase in CGRP content observed in cancer-induced bone pain is mirrored by a central increase in the extracellular levels of CGRP. This increase in CGRP not only may facilitate glutamate-driven neuronal nociceptive signaling but also act on astrocytic CGRP receptors and lead to release of ATP. Abstract : Increased central levels of extracellular calcitonin gene-related peptide and calcitonin gene-related peptide receptors expressed on neurons and astrocytes may facilitate nociception in cancer-induced bone pain.